Evaluation of Some Mechanical Properties of Cola pachycarpa (K. Schum.) Wood in the Tropical Rainforest Ecosystem of Rivers State, Nigeria - Kennedy Aleru; Nwiisuator David-Sarogoro; Burabari Jephter (Drvna Industrija)
The wood mechanical properties of Cola pachycarpa K Schum. were investigated within one of the tropical rainforest ecosystems of Rivers State. Three mature wood stands of Cola pachycarpa were harvested and used for the study. Samples of wood were collected from each of the different sections of the tree: the base (10 % height), middle (50 % height), and top (90 % height) along the axial plane. These samples were then divided into innerwood, corewood, and outerwood based on their radial position. Afterwards, the samples underwent oven drying until they reached a moisture content (MC) level of 12 %. The study was conducted using a 3 × 3 nested design in a completely randomized design (CRD). In cases where there were significant differences, the Duncan multiple range test (DMRT) was employed to separate the means. The results revealed that the MOR mean value was 5.89 N/mm2 with an increase from top to base along the axial plane and with an increase from outer to inner wood across the bole of the tree radially. The MOE mean value was 810.87 N/mm2 and it showed an increase from the base to the top axially, with an increase from the outer to inner wood radially. The mean value of CS//G recorded 34.62 N/mm2. It showed that there was an increase from base to top across the grain radially, and an increase from outer to inner wood. The findings of this study offer quantitative data on the potential use of Cola pachycarpa wood, which could be competitive with other well-known wood species and serve as a good replacement for commercially overexploited wood species.